Multifaceted mechanisms of colistin resistance revealed by genomic analysis of multidrug-resistant Klebsiella pneumoniae isolates from individual patients before and after colistin treatment. Issue 4 (October 2019) - Zhu, Yan; Galani, Irene; Karaiskos, Ilias; Lu, Jing; Aye, Su Mon; Huang, Jiayuan; Yu, Heidi H.; Velkov, Tony; Giamarellou, Helen; Li, Jian
Highlights: 16 K. pneumoniae isolates were from 8 patients before and after colistin treatment. Totally 449 resistance genes were predicted to confer multidrug resistance. An IS Kpn26 -like element disrupted mgrB in 15 of 16 K. pneumoniae isolates. phoQ mutations in 7 colistin-susceptible K. pneumoniae isolates with disrupted mgrB . Secondary PhoQ mutations occurred in mgrB -disrupted, colistin-resistant isolates. Summary: Objectives: Polymyxins (i.e., polymyxin B and colistin) are used as a last-line therapy to combat multidrug-resistant (MDR) Klebsiella pneumoniae . Worryingly, polymyxin resistance in K. pneumoniae is increasingly reported worldwide. This study identified the genetic variations responsible for high-level colistin resistance in MDR K. pneumoniae clinical isolates. Methods: Sixteen MDR K. pneumoniae isolates were obtained from stool samples of 8 patients before and after colistin treatment. Their genomes were sequenced on Illumina MiSeq to determine genetic variations. Results: Fifteen of 16 isolates harboured IS Kpn26 -like element insertion at nucleotide position 75 of mgrB, abolishing its negative regulation on phoPQ ; while colistin-susceptible ATH7 contained intact mgrB and phoQ . Interestingly, each of the 7 mgrB -disrupted, colistin-susceptible isolates contained a nonsynonymous substitution in PhoQ (G39S, L239P, N253T or V446G), potentially impairing its function and intergenically suppressing the effect caused by mgrB inactivation. Additionally, three of the 7 corresponding mgrB -disrupted, colistin-resistant isolates harboured a secondary nonsynonymous substitution in PhoQ (N253P, D438H or T439P). Conclusions: This is the first report of phoQ mutations in mgrB -disrupted, colistin-susceptible K. pneumoniae clinical isolates. We also discovered multiple phoQ mutations in mgrB -disrupted, colistin-resistant strains. Our findings highlight the multifaceted molecular mechanisms of colistin resistance in K. pneumoniae .